Social Media and Orthodontics. (2nd October 2020) - Frawley, Tom; Scott, Paul; Shelton, Andrew; Smith, Alastair
Abstract : Social media has become increasingly relevant to Orthodontics in several ways. This article highlights how both current and prospective patients may utilize social media to access information about, and voice their experiences of, orthodontic treatment. The applications of this to orthodontic research will also be discussed. Orthodontists should be aware of the role of social media in both education and marketing, as well as the current guidance and best practice in these areas. This knowledge should enable clinicians to maximize the advantages and avoid the pitfalls of social media in day-to-day life. CPD/Clinical Relevance: Clinicians should be aware of the potential impact of social media on education, research, marketing and patients' experiences of treatment.